Stable isotope ratio analysis: A potential analytical tool for the authentication of South African lamb meat. (1st February 2016) - Erasmus, Sara Wilhelmina; Muller, Magdalena; van der Rijst, Marieta; Hoffman, Louwrens Christiaan
Highlights: Stable isotope ratios were determined for South African Dorper lambs. Differences in the isotope ratios of lambs from different farms were found. Isotope ratios were indicative of the extensive grazing diet of the lambs. Promising tool developed for the authentication of origin and feeding regime. Abstract: Stable isotope ratios ( 13 C/ 12 C and 15 N/ 14 N) of South African Dorper lambs from farms with different vegetation types were measured by isotope ratio mass spectrometry (IRMS), to evaluate it as a tool for the authentication of origin and feeding regime. Homogenised and defatted meat of the Longissimus lumborum (LL) muscle of lambs from seven different farms was assessed. The δ 13 C values were affected by the origin of the meat, mainly reflecting the diet. The Rûens and Free State farms had the lowest ( p  ⩽ 0.05) δ 15 N values, followed by the Northern Cape farms, with Hantam Karoo/Calvinia having the highest δ 15 N values. Discriminant analysis showed δ 13 C and δ 15 N differences as promising results for the use of IRMS as a reliable analytical tool for lamb meat authentication. The results suggest that diet, linked to origin, is an important factor to consider regarding region of origin classification for South African lamb.